PERLAKUAN TERMOMEKANIS PADUAN TI-6AL-4V - YUZA DIPUTRA , VIKO
Titanium's allotropic transformation allows more diverse strengthening mechanism opportunities. Thermomechanical processing is used to control the microstructure and properties. As titanium a+B alloy, Ti-6Al-4V is possible to increase its hardness by thermomechanical processes. In this research, Ti-6Al-4V alloy consisted of a and B phase was thermally and thermo mechanically treated. Some parameters of thermomechanical treatment (such as rolling temperature, percentage of rolling reduction and interval time to quench after rolling process) were varied to the effect of microstructure and the hardness. Some heat treatment processes and cold work also have been done for a comparison. SEM, EDS and XRD were used to characterize the thermomechanical processes specimen for deeper analysis. Microstructure resulted from thermomechanical treatment are bent a lamellae prior elliptical B grain structure. Furthermore, thermomechanical treatment also affected shape and density of a lamellae. Elongated grain, and needle structure of martensite also revealed from thermomechanical treatment micro-structure. The highest value of hardness (463,1 VHN) resulted from rolled the alloy 40% reduction at B phase temperature (1050 degrees C) and water quench. Its hardness has a higher value) than a heat treatment at temperature 1050 degrees C (431,6 VHN) and cold work (431 VHN) with 40% reduction at room temperature. XRD analysis shows that thermomechanical processes increasing dislocation density and indication of residual stress.